Genetic diversity of the Dwarf honeybee (Apis florea Fabricius, 1787) populations based on microsatellite markers - Asadi, N.; Rahimi, A.; Ghaheri, M.; Kahrizi, D.; Bagheri Dehbaghi, M.; Khederzadeh, S.; Banabazi, M. H.; Esmaeilkhanian, S.; Veisi, B.; Geravandi, M.; Karim, H.; Vaziri, S.; et al. (Cellular and Molecular Biology, 2016)
Apis florea is one of two species of small, wild honeybee. The present study was conducted to evaluate the genetic diversity of Apis florea honeybee from 48 nests (colonies) using microsatellite markers in the South of Iran. All honeybee samples were analyzed for six microsatellite loci (A88, A107, A7, B124, A113 and A35). The six loci had different numbers of alleles in the sampled colonies ranging from 7 (loci A107) to 3 (loci A7, A35). Gene diversity in Apis florea ranged from 0.491 to 0.595. This range probably reflects the spreading of nests in a large region with a varied climate. Phylogenetic tree showed two distinct clusters including a) Minab region samples and b) Bandar Abbas, Bandar Khamir and Qeshm Island regions. All of these regions are geographically rich, having varied vegetation and climate conditions. Our findings are an important contribution to the methods of studying distribution and conservation of Apis florea.